The effects of context of learning on the perception of Spanish stress by Japanese speakers - Sierra, Elkin; Loyola, Gabriela Martinez; Kimura, Takuya; Stevenson, Ryan; Rao, Rajiv; Rafat, Yasaman (Journal of Speech Sciences, 2023)
This study explores the effect of context of learning on the perception of Spanish lexical stress. Spanish is considered a mixed system (with predictable and unpredictable stress) and a stress-accent language. Tokyo Japanese is a good example of a language without stress, but with pitch-accent. Two groups of Japanese speakers (20 in Bogotá and 25 in Japan) and a control group of 20 Spanish speakers completed a stress identification task, consisting of nine sets of 3 syllable accentual minimal triplets with each having an oxytone (e.g., nabidó), a paroxytone (e.g., nabido), and a proparoxytone (e.g., nábido). The results demonstrated that there was a significant effect of context of learning, with learners in Japan (88%) having a significantly (p=0.000) higher error rate than the learners in Colombia (60%). This study sheds highlights the effect of context of learning on L2 speech learning by demonstrating that immersion can enhance L2 stress perception.